رادە لە گرێى ناویدا - توفیق, قەیس کاکل (Sulaimani Journal for Humanities, 2003)
The title of the research is quantity in noun phrase. Most of kurdish grammatical sources shed light on this subject. These sources distinguish the words of quantity on the base of traditional grammar, the words like (some, many, few, little,....etc.). In this study we indicated a new view on the basis of morpheme theory and descriptive linguistics, we proved the view. This is due to making syntactic patterns for producing quantity in kurdish language.